2015
DOI: 10.4103/2156-7514.172976
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Features of a Juxtaglomerular Cell Tumor

Abstract: Objective:To retrospectively determine whether magnetic resonance imaging (MRI) findings can help differentiate a juxtaglomerular cell tumor (JCT) from clear cell renal cell carcinoma (ccRCC).Materials and Methods:Eight patients with JCTs and 24 patients with pathologically proven ccRCC were included for image analysis. All patients underwent unenhanced MRI and dynamic contrast-enhanced MRI. Fat-suppressed T2-weighted imaging (T2WI), diffusion-weighted imaging (DWI), in- and opposed-phase imaging, and fat-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…The diffusion-WIs are related to the motion of water molecules and are highly sensitive for small lesions. All three JGCTs, including tumors as small as 0.7 cm × 0.7 cm, were significantly hyperintense on diffusion-WIs, as described previously (5,18). Unlike contrast CT, MRI provides more modalities, without enhancement, and does not affect the kidney function.…”
Section: Multiple Imaging Modalities In the Diagnosis Of Jgctsupporting
confidence: 67%
“…The diffusion-WIs are related to the motion of water molecules and are highly sensitive for small lesions. All three JGCTs, including tumors as small as 0.7 cm × 0.7 cm, were significantly hyperintense on diffusion-WIs, as described previously (5,18). Unlike contrast CT, MRI provides more modalities, without enhancement, and does not affect the kidney function.…”
Section: Multiple Imaging Modalities In the Diagnosis Of Jgctsupporting
confidence: 67%
“…The reported features include iso-intensity or mild hyperintensity on T2-weighted imaging, heterogeneous hyperintensity on diffusionweighted imaging, and a degree of enhancement <200% in the corticomedullary phase. 9 The tumor size typically ranges from 2-5 cm as was seen in our case with the tumor measuring 2.4 cm in greatest dimension, but larger sizes have been reported. Imaging results demonstrating a renal mass in younger individuals usually prompts testing of aldosterone and renin levels if these are not tested in the early stages of the workup.…”
Section: Discussionmentioning
confidence: 52%
“…Tanabe A et al also reported high-density renal mass in the plain CT scan for JGCT ( 17 ). For magnetic resonance imaging (MRI), Kang et al ( 18 ) report that iso-intensity or mild hyperintensity on T2WI, a lower ADC value (heterogeneous hyperintensity) on DWI, and a degree of enhancement <200% in the corticomedullary phase were the major MRI findings for JGCTs. Renal angiography can identify whether the hyperreninemia is caused by renal artery stenosis.…”
Section: Discussionmentioning
confidence: 99%